Open yard mobile racking system for precast lightweight panel storage - Che Mohd Saleh, Muhammad Hafiizhuddin Naim (2022)
The demand for precast lightweight is increasing the need for a storage system that is more effective than a conventional method. To fulfill the need, a better innovation is required to create. The mobile racking system is one of the suggested ideas that can solve a problem regarding the increasing demand, safety, and quality of the precast lightweight product. The Proposed innovation is research by collecting data from literature review and simulation method. The duration of time given is used wisely to collect the data through previous research and create a simulation of the product when it is operating. From the finding, there are two main problems: the safety and quality of the product while stored in an open yard or storage area. From the finding, a prototype of a model mobile racking system is created through 3d software. In conclusion, product innovation will solve the problem, but more detailed research needs to be discussed in the future.